2014
DOI: 10.1136/bmjopen-2014-005696
|View full text |Cite
|
Sign up to set email alerts
|

The current provision of community-based teaching in UK medical schools: an online survey and systematic review

Abstract: ObjectiveTo evaluate the current provision and outcome of community-based education (CBE) in UK medical schools.Design and data sourcesAn online survey of UK medical school websites and course prospectuses and a systematic review of articles from PubMed and Web of Science were conducted. Articles in the systematic review were assessed using Rossi, Lipsey and Freeman's approach to programme evaluation.Study selectionPublications from November 1998 to 2013 containing information related to community teaching in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
(78 reference statements)
0
25
0
Order By: Relevance
“…Early exposure of students to general practice and other community settings provides students with increased insight into patient‐centred medicine, improves continuity of care and enhances communication skills . This approach has been shown to increase students' interest in general practice as a career choice – an important outcome given the UK's changing demographics and an accompanying shift in emphasis from management to prevention . Further studies from Thailand, Jordan, Australia, Canada and the USA have shown that community‐oriented training in undergraduate medical education through specific programmes or standalone rural schools provides students with better understanding of community needs, hands‐on experience and exposure to health issues that are locally relevant, and can generate a sense among students of being valued by the community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early exposure of students to general practice and other community settings provides students with increased insight into patient‐centred medicine, improves continuity of care and enhances communication skills . This approach has been shown to increase students' interest in general practice as a career choice – an important outcome given the UK's changing demographics and an accompanying shift in emphasis from management to prevention . Further studies from Thailand, Jordan, Australia, Canada and the USA have shown that community‐oriented training in undergraduate medical education through specific programmes or standalone rural schools provides students with better understanding of community needs, hands‐on experience and exposure to health issues that are locally relevant, and can generate a sense among students of being valued by the community.…”
Section: Resultsmentioning
confidence: 99%
“…14 British medical schools include community-based education as a component of medical education, with a variety of teaching methods employed to promote better understanding of health concerns at the community level. 15 Early exposure of students to general practice and other community settings provides students with increased insight into patient-centred medicine, improves continuity of care and enhances communication skills. 15 This approach has been shown to increase students' interest in general practice as a career choicean important outcome given the UK's changing demographics and an accompanying shift in emphasis from management to prevention.…”
Section: Health Equitymentioning
confidence: 99%
“…The trend today is that an increasing share of medical students’ learning takes place in primary healthcare (PHC) [1]. This is the natural result of the changes in many of our healthcare systems, where most patients are taken care of in healthcare units outside the hospitals, which makes common conditions rare at our hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Sociological perspectives need to be incorporated into the traditional biomedical curriculum to produce competency-based and community-oriented physicians. Many schools have entirely restructured their curricula with a community-oriented approach, and other medical institutions have also made significant changes by introducing a communitybased element into their curriculum (18,19). A study conducted in the UK found that out of the 32 undergraduate UK medical schools, 31 provided a variety of community-based education (CBE) training (20).…”
mentioning
confidence: 99%